Hydrolysis of flavonoid glycosides of aqueous extract of Octomeles Sumatranus and its antioxidant activities / Farah Ad-Din Nordin - Nordin, Farah Ad-Din (Faculty of Applied Sciences, 2009)
The extract of Octomeles Sumatranus has been used by the Sarawak and Sabah natives as health tonic. An attempt has been made to chemically profile the extract using LC-MS but the types of flavonoids cannot be determined since the flavonoids glycosides compounds contain many sugars. Therefore, the glycosides were hydrolysed for 3 hours at 80°C and the resulting aglycones were identified using LCMS. The conditions for analyzing the aglycones at HPLC and LC-MS were the same. The hydrolysis was a success based on the differences from the retention time of the unhydrolyzed and hydrolyzed extract. The Rt of the unhydrolyzed extract was 15 minutes while the Rt of the hydrolyzed extract was 30 minutes. The hydrolyzed extract was later being submitted to LC-MS for identification and structural determination of the aglycones. The MH+ peak was m/z 365.26 which shows the possible molecular weight of the aglycones. The antioxidant activities of Octomeles Sumatranus were investigated based on free radical scavenging activity, DPPH. The IC50 of the unhydrolyzed extract was detectable at 517 nm and the value was determined to be 19 |ig/mL.